Systemic Lupus Erythematosus (SLE) in a male patient previously diagnosed as Adult Onset Still’s Disease: A Case Report (Bangladesh Journal of Medicine, 2019)
Adult-onset Still’s disease (AOSD) is a rare clinical entity with unknown etiology, characterized by evanescent rash, arthritis, fever, and other systemic presentation. In this case report, we describe a male patient of 50 years, previously diagnosed as a case of Adult onset still’s disease based on Yamaguchi criteria after the exclusion of other potential diagnoses. Later he was admitted into the Medicine department of Chittagong Medical College Hospital where he was found to have serological features of Systemic lupus erythematosus, another very much uncommon autoimmune disorder in male. On several occasion of his past admissions, SLE and RA were excluded meticulously. He initially responded to oral steroids only, recurrence of symptoms led us to work on the underlying etiology further. Coexistence of SLE in a patient with AOSD is not so commonly found. In our case, we notice this interesting phenomenon which was crucial for his management.Bangladesh J Medicine July 2019; 30(2) : 100-103